Using Giant Pulses to Measure the Impulse Response of the Interstellar Medium - Nikhil Mahajan; Marten H. van Kerkwijk (The Astrophysical Journal, 2023)
Giant pulses emitted by PSR B1937+21 are bright, intrinsically impulsive bursts. Thus, the observed signal from a giant pulse is a noisy but direct measurement of the impulse response from the ionized interstellar medium. We use this fact to detect 13,025 giant pulses directly in the baseband data of two observations of PSR B1937+21. Using the giant pulse signals, we model the time-varying impulse response with a sparse approximation method, in which the time dependence at each delay is decomposed in Fourier components, thus constructing a wavefield as a function of delay and differential Doppler shift. We find that the resulting wavefield has the expected parabolic shape with several diffuse structures within it, suggesting the presence of multiple scattering locations along the line of sight. We also detect an echo at a delay of about 2.4 ms, over 1.5 times the rotation period of the pulsar, which moves along the trajectory expected from geometry between the two observations. The structures in the wavefield are insufficiently sparse to produce a complete model of the system; hence, the model is not predictive across gaps larger than about the scintillation time. Nevertheless, within its range, it reproduces about 75% of the power of the impulse response, a fraction limited mostly by the signal-to-noise ratio of the observations. Furthermore, we show that by deconvolution, using the model impulse response, we can successfully recover the intrinsic pulsar emission from the observed signal.